Study of the Interaction of Some Potential Anticancer Gold(III) Complexes with Biologically Important Thiols Using NMR, UV–Vis, and Electrochemistry. Issue 6 (10th April 2017) - Omer, Khalid H.; Seliman, Adam A. A.; Al‐Mohsin, Hassan A.; Kawde, Abdel‐Nasser; Altaf, Muhammad; Wazeer, Mohammed I. M.; Ahmad, Saeed; Musa, Musa M.; Isab, Anvarhusein A.
ABSTRACT: The interaction of gold(III) complexes [Au(en)Cl2 ]Cl, [Au(en)2 ]Cl3, [Au( cis ‐DACH)Cl2 ]Cl, and [Au( cis ‐DACH)2 ]Cl3 (en = ethylenediamine, DACH = cis ‐1, 2‐diaminocyclohexane) with biologically important thiols, such as glutathione (GSH), dl ‐penicillamine (PSH), mercaptoacetic acid (MAA), and N ‐(2‐mercaptopropionyl)glycine (MPG), has been studied using 1 H, 13 C NMR, UV–vis spectroscopy and electrochemistry in aqueous solution. Kinetic data revealed that the reactivity of their substitution reaction followed the order: [Au(en)Cl2 ] + > [Au(en)2 ] 3+ > [Au( cis ‐DACH)Cl2 ] + > [Au( cis ‐DACH)2 ] 3+ . The thiol reactivity increased with decreasing its size, viz. MAA ≫ MPG > PSH > GSH. Square wave stripping voltammetry displayed peaks for Au(III) and Au(I) at +0.875 V and +1.4 V respectively. The interaction of the complexes with thiols resulted in reduction of gold(III) to gold(I) and thiol ligands (RSH) were oxidized to disulfide (RSSR).